HUBUNGAN PENGETAHUAN, SIKAP, DAN PERILAKU GIZI SEIMBANG DENGAN KEJADIAN OBESITAS PADA REMAJA DI SMA NEGERI 5 SAWANGAN KOTA DEPOK - Sylvianis Widyastuti, (2022)
In 2018, the prevalence of obesity in adolescents in Depok is 4.86% at aged 13-15 years and 5.75% at aged 16-18 years. This high prevalence of obesity can be regarded as an indicator of a lack of nutritional knowledge. Nutritional knowledge needed to combine nutritional information with eating behavior, so that a good knowledge about nutrition and health can be developed. Besides that, important components that affects obesity is attitudes and behavior towards a healthy lifestyle. This study aims to determine the relationship between knowledge, attitudes, and behavior of balanced nutrition with obesity in adolescents at SMA Negeri 5 Depok City. This study used a cross sectional design among 110 respondents determined by simple random sampling technique. Data collected using a balanced nutrition knowledge, attitude, and behavior questionnaire. The results shows that 11.8% of adolescents were obese, 16.0% had good knowledge of obesity, 13.0% had positive attitudes towards obesity, and 15.3% had positive behavior towards obesity. Relationship analysis performed using Chi Square test showed that there was no relationship between knowledge of balanced nutrition (p = 0.215), balanced nutrition attitude (p = 0.715), and balanced nutrition behavior (p = 0.230) with obesity in adolescents at SMA Negeri 5 Depok City.